Solvent extraction, spectral analysis and antibacterial activity of the bioactive crystals of Sargassum aquifolium (Turner) C.Agardh from Red Sea. Issue 8 (3rd April 2021) - Moni, Sivakumar Sivagurunathan; Alam, Mohammad Firoz; Makeen, Hafiz A.; Alhazmi, Hassan A.; Sultan, Muhammad; Siddiqui, Rahimullah; Jabeen, Aamena; Sanobar, Syeda; Alam, Md Shamsher; Rehman, Zia Ur; Elmobark, Mohamed Eltyep; Madkhali, Osama; et al.
Abstract: The purpose of this study was to investigate the chemical composition and anti-bacterial properties of the bioactive principles of Sargassum aquifolium (Turner) C.Agardh, a brown seaweed in Red sea of Jazan province, Kingdom of Saudi Arabia. Crystals were obtained from the petroleum ether extract of Sargassum aquifolium and subjected to chemical tests, FTIR spectroscopic analysis and NMR analysis to identify their chemical composition, and to study their antibacterial properties against selected human pathogenic bacteria. In addition, GC–MS analysis was performed to identify the bioactive compounds in the crude petroleum ether extract. Results of the antibacterial effect of the crystal analyte showed a wide spectrum of activity against the screened human pathogenic bacteria. Graphical Abstract: